Skin hydration modulatory activities of Ficus deltoidea extract - Ariffin, Nor Hazwani Mohd; Hasham, Rosnani; Hamzah, Mohd Amir Asyraf Mohd; Park, Chang Seo (Fitoterapia, 2024)
Ficus deltoidea was known for its potent antioxidant, anti-melanogenic and photoprotective skin barrier activities. These properties are contributed by its biomarkers which are vitexin and isovitexin. This study aims to optimize the yield of methanolic extraction of Ficus deltoidea leaves (EFD) and evaluate their effects on skin barrier function and hydration. For optimization, Box-Behnken design was utilized to investigate the effects of methanol concentration, sonication time, and solvent-to-sample ratio on the yields of vitexin and isovitexin in EFD. The optimal yields obtained were 32.29 mg/g for vitexin and 35.87 mg/g for isovitexin. The optimum extraction conditions were 77.66% methanol concentration, 20.03 min sonication time, and 19.88 mL/g solvent-to-sample ratio. The quantitative real-time polymerase chain reaction was utilized to measure variant marker genes of transglutaminase-1, caspase 14, ceramide synthase 3, involucrin, and filaggrin of EFD-induced keratinocyte differentiation by in vitro study. Exposure to EFD has elevated the mRNA levels of all tested marker genes by 0.7-9.2 folds. Then, in vivo efficacy study was conducted on 20 female subjects for 14 days to evaluate skin biophysical assessment of hydration. EFD topical formulation treatment successfully increased skin hydration on day 7 (43.74%) and day 14 (47.23%). In silico study by molecular docking was performed to identify intermolecular binding interactions of vitexin and isovitexin with the interested proteins of tested marker genes. The result of molecular docking to the interested proteins revealed a similar trend with real-time PCR data. In conclusion, EFD potentially enhanced the skin barrier function and hydration of human skin cells.